2017
DOI: 10.2147/ijn.s115215
|View full text |Cite
|
Sign up to set email alerts
|

Transferrin receptor-targeted pH-sensitive micellar system for diminution of drug resistance and targetable delivery in multidrug-resistant breast cancer

Abstract: The emergence of drug resistance is partially associated with overproduction of transferrin receptor (TfR). To overcome multidrug resistance (MDR) and achieve tumor target delivery, we designed a novel biodegradable pH-sensitive micellar system modified with HAIYPRH, a TfR ligand (7pep). First, the polymers poly( l -histidine)-coupled polyethylene glycol-2000 (PHIS-PEG 2000 ) and 7pep-modified 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-polyethylene glycol-2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…In a study conducted by Gao et al., a biodegradable pH‐sensitive micellar doxorubicin DDV was devised with the surface conjugation of a modified seven peptide transferrin receptor ligand (7pep; amino‐acid sequence: HAIYPRH) . Doxorubicin encapsulating micelles composed of 7pep conjugated 1,2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine and polyethylene glycol‐2000 (DSPE‐PEG 2000 ) were used in nude mice bearing drug‐resistant MCF‐7 xenografts (MCF‐7/Adr) which overexpress Tfr . Micelles were evaluated for internalization and therapeutic effect at formulations of varying 7pep modification (10%, 30%, 50%, 60% 7pep).…”
Section: Receptor Targets For Drug Resistant Tumorsmentioning
confidence: 99%
“…In a study conducted by Gao et al., a biodegradable pH‐sensitive micellar doxorubicin DDV was devised with the surface conjugation of a modified seven peptide transferrin receptor ligand (7pep; amino‐acid sequence: HAIYPRH) . Doxorubicin encapsulating micelles composed of 7pep conjugated 1,2‐distearoyl‐sn‐glycero‐3‐phosphoethanolamine and polyethylene glycol‐2000 (DSPE‐PEG 2000 ) were used in nude mice bearing drug‐resistant MCF‐7 xenografts (MCF‐7/Adr) which overexpress Tfr . Micelles were evaluated for internalization and therapeutic effect at formulations of varying 7pep modification (10%, 30%, 50%, 60% 7pep).…”
Section: Receptor Targets For Drug Resistant Tumorsmentioning
confidence: 99%
“…Gao et al designed a micellar system called 7-pep HD micelles, and the in vitro study on MCF/Adr cells and in vivo study on MDR tumors-loaded female nude mice indicated that these biodegradable micelles can effectively target the MDR tumor whose surface overexpresses transferrin and overcomes MDR. 87 Gastric cancer tends to overexpress MiR-21; to combat this condition, Wu et al developed a novel nano-delivery system called anti-miRNA oligonucleotide-21-human epidermal growth factor receptorpoly(ethylene glycol)-poly(ε-caprolactone) nanoparticles, and then used it to encapsulate trastuzumab to target gastric cancer cells in vitro and in vivo. 88 As a result, gastric cancer cells were more sensitive to drugs, and this demonstrated the enormous potential of antibody-dependent targeted transport.…”
Section: Polymeric Micellesmentioning
confidence: 99%
“…The pH at the surface of highly metastatic cells within tumors was found to be even more acidic, about 6.1–6.4 . Some pH‐sensitive micelles have been developed for efficient intracellular delivery in response to endolysosomal pH (pH endo : 6.0‒5.0) . Despite some of the particles being successfully endocytosed by the tumor cells, most of them become trapped in acid endolysosomes and are unable to release the drug .…”
Section: Introductionmentioning
confidence: 99%